The Pluralistic Problematic: William James and the Pragmatics of the Pluriverse. (March 2021) - Savransky, Martin
In his lectures on pragmatism, William James famously proposed that the question of 'the one and the many' constitutes the most central of all philosophic problems, and that it is 'central because so pregnant'. Prompted by James' proposition, this article explores the intimately political connection in James' thought between his pluralistic metaphysics and the nature of the problematic as a generative force that impregnates worlds and thoughts with differences: what I here call 'the pluralistic problematic'. Exploring the generative significance of the problematic in James' philosophy, I propose that, where James is concerned, the pluriverse has a thoroughly problematic mode of existence. And pluralism, rather than a celebration of the many, rather than a philosophical exposition on multiple worlds and ontologies, or a theory of the organisation of a diverse polis, is first and foremost a pragmatics of the pluriverse – a political, experimental and pragmatic response to the ongoing insistence of the pluralistic problematic.